2001
DOI: 10.1557/proc-688-c1.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Crystallization of Pb(Zr0.4,Ti0.6)O3 Thin Films by Chemical Solution Deposition

Abstract: We studied the crystallization of sol-gel derived Pb(Zr0.4Ti0.6)O3 [PZT(40/60)] thin films at 400 down to 390°C on Pt/SiO2/Si substrates by combination of diol-based solutions and modified film preparation processes. It was found that PZT films could be crystallized at 390°C and that PZT films crystallized at 400°C had microstructures with perovskite-single-phase columnar grains and good ferroelectric characteristics such as switched polarization (2 Pr) of 20 μC/cm2 and relative permittivity (εr) of 740. Next,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5] Various CSD methods are broadly divided into those involving a reaction leading to a heterometallic precursor, such as (organic) sol-gel, or polymeric precursor routes in water-based media or those based on mixing of non-reactive organic compounds, i.e. metalloorganic decomposition (MOD).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Various CSD methods are broadly divided into those involving a reaction leading to a heterometallic precursor, such as (organic) sol-gel, or polymeric precursor routes in water-based media or those based on mixing of non-reactive organic compounds, i.e. metalloorganic decomposition (MOD).…”
Section: Introductionmentioning
confidence: 99%
“…Drouin et al [2] reported that it was possible to obtain local heating of a platinum silicide film around 300-450°C using a standard scanning electron microscopy (SEM) system. Maki et al [3] and Huang et al [1] also report a low temperature-phase formation of a sol-gel derived PZT film around 400-420°C. Furthermore, electron beam lithography has been considered as a potential alternative to optical lithography for critical level patterning in integrated-circuit manufacturing such as nanoelectromechanical systems (NEMS) and FeRAMs [4,5].…”
Section: Introductionmentioning
confidence: 93%